Design And Analysis Of Diesel Generator With Battery Storage For Microgrid System - Khamis, Aziah; Mohd Aras, Mohd Shahrieel; Mohd Shah, Hairol Nizam; Ab Rashid, Mohd Zamzuri; Mohd Zambri, Mohd Khairi; Ahmad, Azhar; Nor Rahim, Mohd Akmal Hakim (IJSRET, 2017)
Nowadays, distributed generation innovation required picked up a greater amount by many countries. Recently, there would a many issue for power system. A standout amongst those issue is high electricity price. Those cost Previously, energy generation depend generally on the sort also market value of the fuel used, government subsidies, goverment and industry regulation, furthermore actually local climate patterns. Other than that, utilization of fossil fuel necessary on a chance to be cuts. By utilizing those fossil fuel, it will result in the exhaust cloud and corrosive downpour. Subsequently that, it will result in the greenhouse emanation and earth's environmental will shift. So as with supply a better power system, this report introduces an model about Diesel Generator (DG) and a battery storage microgrid (MG) system. The DG may be the little scale which broadly utilized within power generation system. DG can work for renewable also non-renewable energy. Through this project, DG will be design toward utilizing DG and battery storage system. Those DG system will make Analysis for grid connected.